Synthesis, characterization and electrochemistry of new type soluble porphyrazine containing 3-phenylpropylthio substituent - (:unkn) unknown (POLISH CHEMICAL SOC, 2008)
Octakis(3-phenylpropylthio) porphyrazines MPz(SR)(8), where (M = Mg, H, Ni, Zn, Co) and R = C9H11, were synthesized starting with the corresponding unsaturated dicarbonitrile derivative. These new compounds have been investigated and characterized by UV, FT-IR, H-1 NMR, GC-MS and elemental analysis methods. As in the case of the unmetalated species, [H(2)Pz], three reversible one-electron reductions and one reversible oxidation process (two for Co(II)Pz) were observed for all of the metal complexes. The E-1/2 values are similar for the H(2)Pz, Ni(II)Pz and Zn(II)Pz derivatives with negative shift due to the different effective charges of the central metal ion. Peak to peak separations and separation between the first reduction and first oxidation couples related with the HOMO-LUMO gap of the complexes are in harmony with the common porphyrazine complexes.
Keywords: porphyrazine; electrochemistry; cobalt; nickel; zinc; METAL-COMPLEXES